2002
DOI: 10.1097/00129689-200206000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-assisted Resection of Complicated Meckel's Diverticulum in Adults

Abstract: The era of videoendoscopic surgery in emergency surgery practice has facilitated a wide range of endoscopic operative procedures. In our unit the diagnosis of acute abdomen is made after sequential clinical and laboratory examination, and diagnostic laparoscopy is advocated. Laparoscopy-assisted resection of complicated Meckel's diverticulum in two adult patients was performed, and the results are discussed. Between December 1996 and June 2000, 98 patients underwent diagnostic laparoscopy at the Cerrahpasa Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…Com o aumento da experiência na utilização do método, a abordagem da obstrução intestinal por VL foi sendo cada vez mais empregada, e as intervenções tanto diagnósticas como terapêuticas puderam ser realizadas nestes pacientes com mais liberalidade [8][9][10] . Após relatos publicados de tratamento por VL de obstruções intestinais secundárias a bezoares, divertículos de Meckel, aderências e vários tipos de hérnias, os cirurgiões passaram a considerar a obstrução intestinal como contra-indicação apenas relativa ao método 11,12 .…”
Section: Introductionunclassified
“…Com o aumento da experiência na utilização do método, a abordagem da obstrução intestinal por VL foi sendo cada vez mais empregada, e as intervenções tanto diagnósticas como terapêuticas puderam ser realizadas nestes pacientes com mais liberalidade [8][9][10] . Após relatos publicados de tratamento por VL de obstruções intestinais secundárias a bezoares, divertículos de Meckel, aderências e vários tipos de hérnias, os cirurgiões passaram a considerar a obstrução intestinal como contra-indicação apenas relativa ao método 11,12 .…”
Section: Introductionunclassified
“…As this occurs, the yolk sac also begins to atrophy (11). In 0.3% to 2.5% of the population, this vitelline duct persists to become a Meckel's Diverticulum (1,11). The yolk sac is supplied by 2 vitelline arteries, one of which degenerates as the yolk sac atrophies, while the remaining artery develops into the superior mesenteric artery (11).…”
Section: Discussionmentioning
confidence: 99%
“…Meckel's diverticulum is the most common congenital abnormality of the gastrointestinal tract, affecting 2% of the general population (1)(2)(3). Most of the Meckel's diverticula are discovered incidentally during the surgical procedures performed for other reasons.…”
mentioning
confidence: 99%
“…Divertculectomy was done after mini-laparotomy and exteriorization which is an acceptable approach. Altinli et al reported extracorporeal transumbilical resection of the Meckel's diverticulum with handsewn anastomosis [13]. Saggar et al described with the laparoscope, both extracorporeal (LATUM i.e.…”
Section: Discussionmentioning
confidence: 99%